Diversity Detection of Speckles for Double-Wavelength Interferometry on Rough Surfaces - Leuchs, Gerd; et al. (Applied Optics, 2002)
When the topography of a rough surface is measured with a double-wavelength interferometer, the phase error of the signal corresponding to the synthetic wavelength increases in the vicinity of dark speckles. To overcome this problem we perform an amplitude-dependent averaging of the synthetic phase over independent speckles (diversity detection). We either use spatially neighboring speckles or in the case of depolarizing surfaces, we use speckles of the same spatial mode, but with orthogonal polarizations. For the latter case the lateral resolution stays unaffected. The reduction of the speckle noise is demonstrated experimentally for a laterally scanning double-wavelength interferometer with superheterodyne detection of the synthetic phase. © 2002 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.divers